Multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties and its preparation method and application
By building a peak-to-valley structure and anti-fouling layer of multi-layer composite materials on the ship, the problems of biological pollution and easy material damage are solved, and more stable drag reduction and anti-fouling effects are achieved, reducing friction resistance and extending service life is extended. .
Patent Information
- Application Number
- CN202411062197.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The prior art is difficult to effectively prevent the increase in friction resistance caused by biological contamination on large transport ships, and the elastic strength of the imitation dolphin skin material is poor, easy to break and fall off, and difficult to use for a long time.
The preparation method of multi-layer composite materials includes constructing a hybrid connection layer with peak-to-grough structure layer by layer on the substrate, an active anti-fouling flexible drag reduction layer and a passive anti-fouling elastic drag reduction layer, through silane coupling agent and nanometers The reaction of particles, epoxy resin, fluorocarbon resin, polyurethane, strong polar monomer, initiator, polysiloxane and catechol compounds forms a composite material with multiple antifouling and synergistic flexibility to strengthen the drag reduction characteristics.
Improve the stability and service life of the material, effectively suppress pressure pulsation, absorb kinetic energy of the external flow field, reduce friction resistance, block bacteria and algae in seawater, reduce the increase in friction resistance caused by biological pollution, and realize the ship's Anti-fouling, drag reduction and speed-up.
Smart Images

Figure CN118558568B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a multilayer composite material, in particular to a multilayer composite material with multiple antifouling coordinated flexible enhanced drag reduction properties and a preparation method and application thereof, belonging to the technical field of marine drag reduction materials. Background Art
[0002] During the operation of water vessels and underwater ships, the speed is reduced and the energy consumption is increased. Flexible drag reduction technology uses the soft and elastic skin of dolphins as a bionic source. As a marine mammal, dolphins have the ability to swim at high speed. The skin of dolphins is soft and elastic, and there are papillary protrusions under the epidermis that are used to sense water pressure, with an average roughness of 5.1 μm. Dolphins adapt to the external flow field pressure by controlling the contraction or expansion of these tissues to form wrinkles on the skin surface, effectively suppressing pressure pulsation, while absorbing the kinetic energy of the external flow field acting on the flexible coating, increasing the upper limit of the Reynolds number and the stability of the boundary layer for the transition from laminar flow to turbulent flow in the external flow field, delaying the transition from laminar flow to turbulent flow, and reducing friction resistance. However, the elastic materials that imitate dolphin skin are often weak in strength, easy to break and fall off, and the material fails. In addition, dolphins are often in a swimming state, and their elastic and smooth skin can prevent the attachment of biomass, inhibit biological pollution, and avoid the increase in friction resistance caused by biological pollution. However, large transport ships have long downtime, and it is difficult to resist biological pollution by relying solely on elastic and smooth material surfaces. Summary of the invention
[0003] The main purpose of the present invention is to provide a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0004] Another object of the present invention is to provide an application of the multi-layer composite material having multiple antifouling synergistic flexibility and enhanced drag reduction properties.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0006] The embodiment of the present invention provides a method for preparing a multilayer composite material with multiple antifouling coordinated flexible enhanced drag reduction properties, which comprises:
[0007] A first mixed reaction system comprising a silane coupling agent, a two-dimensional sheet material, nanoparticles, an epoxy resin, a fluorocarbon resin and a mixed solvent is subjected to a first reaction and applied to a surface of a substrate to obtain a hybrid connection layer having a peak-valley structure;
[0008] A second mixed reaction system comprising polyurethane, a strongly polar monomer, an initiator and a mixed solvent is subjected to a second reaction in a protective atmosphere to obtain a flexible composite hydrogel; and the flexible composite hydrogel is applied to the surface of a hybrid connection layer having a peak-valley structure, cured, and then immersed in a metal salt aqueous solution for static reaction to obtain an active antifouling flexible drag reduction layer;
[0009] A third mixed reaction system comprising polyurethane, polysiloxane, a catechol compound and a mixed solvent is subjected to a third reaction to obtain a microphase separation composite solution; the microphase separation composite solution is arranged at intervals on the surface of the active anti-fouling flexible drag reduction layer and solidified, thereby forming elastic drag reduction units arranged at intervals on the surface of the active anti-fouling flexible drag reduction layer to obtain a passive anti-fouling elastic drag reduction layer, thereby preparing a multilayer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties.
[0010] In some embodiments, the preparation method includes: placing a mask on the surface of the active anti-fouling flexible drag reducing layer, coating the microphase separation composite solution, and then curing to obtain the passive anti-fouling elastic drag reducing layer.
[0011] An embodiment of the present invention also provides a multilayer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties prepared by the aforementioned preparation method, which includes a hybrid connection layer, an active anti-fouling flexible drag reduction layer and a passive anti-fouling elastic drag reduction layer stacked in sequence on a substrate.
[0012] The embodiments of the present invention also provide the application of the aforementioned multi-layer composite material with multiple antifouling and coordinated flexible enhanced drag reduction properties in the field of antifouling or drag reduction and speed increase.
[0013] Compared with the prior art, the beneficial effects of the present invention include:
[0014] 1) The hybrid connection layer with a peak-valley structure in the multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties prepared by the present invention can improve the bonding strength of the active antifouling flexible drag reduction layer and the passive antifouling elastic drag reduction layer on the substrate, thereby improving the stability of the drag reduction composite material and extending its service life;
[0015] 2) The present invention uses a mask plate to obtain an elastic drag-reducing surface with a thickness step. The thickness gradient and elasticity cooperate to adapt to the external flow field pressure, which can effectively suppress pressure pulsation and absorb the kinetic energy of the external flow field acting on the elastic coating. The upper limit of the Reynolds number for the transition from laminar flow to turbulent flow and the stability of the boundary layer of the external flow field are increased. The transition position from laminar flow to turbulent flow is delayed, the friction resistance is reduced, and the drag reduction capability is improved.
[0016] 3) The active anti-fouling flexible drag reduction layer and the passive anti-fouling elastic drag reduction layer in the present invention work together to block bacteria, barnacles, algae and other substances in seawater from forming conditional films on the surface of the drag reduction material, thereby inhibiting biological fouling and reducing the problem of increased friction resistance caused by biological fouling;
[0017] 4) The present invention reduces the problem of increased friction resistance caused by biological fouling through multi-layer complementary advantages, multi-functional coupling, the anchoring effect of the peak-valley structure of the synergistic hybrid connection layer, the drag reduction characteristics of the elastic drag reduction surface with thickness steps, and active anti-fouling and passive anti-fouling, and finally obtains a stable composite material with multiple anti-fouling synergistic flexible enhanced drag reduction characteristics, which can be used to achieve anti-fouling, drag reduction and speed-up of water vessels, underwater ships, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 It is a schematic structural diagram of a multilayer composite material with multiple antifouling synergistic flexibility and enhanced drag reduction properties in a typical embodiment of the present invention.
[0020] Figure numerals: 1 - substrate, 2 - hybrid connection layer, 3 - active anti-fouling flexible drag reduction layer, 4 - passive anti-fouling elastic drag reduction layer. DETAILED DESCRIPTION
[0021] In view of the problems existing in the above-mentioned prior art, after long-term research and a large number of experiments, the inventor of this case proposed this technical solution, which mainly provides a composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties. The composite material is a bottom-up hybrid connection layer, an active anti-fouling flexible drag reduction layer, and a passive anti-fouling elastic drag reduction layer built layer by layer on a substrate. The multiple layers complement each other's advantages and are multifunctionally coupled, and finally a composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties is obtained, which can be used to achieve anti-fouling, drag reduction and speed-up of water vessels, underwater ships, etc.
[0022] The technical solution, its implementation process and principle will be further explained as follows.
[0023] As one aspect of the technical solution of the present invention, a method for preparing a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties involves:
[0024] A first mixed reaction system comprising a silane coupling agent, a two-dimensional sheet material, nanoparticles, an epoxy resin, a fluorocarbon resin and a mixed solvent is subjected to a first reaction and applied to a surface of a substrate to obtain a hybrid connection layer having a peak-valley structure;
[0025] A second mixed reaction system comprising polyurethane, a strongly polar monomer, an initiator and a mixed solvent is subjected to a second reaction in a protective atmosphere to obtain a flexible composite hydrogel; and the flexible composite hydrogel is applied to the surface of a hybrid connection layer having a peak-valley structure, cured, and then immersed in a metal salt aqueous solution for static reaction to obtain an active antifouling flexible drag reduction layer;
[0026] A third mixed reaction system comprising polyurethane, polysiloxane, a catechol compound and a mixed solvent is subjected to a third reaction to obtain a microphase separation composite solution; the microphase separation composite solution is arranged at intervals on the surface of the active anti-fouling flexible drag reduction layer and solidified, thereby forming elastic drag reduction units arranged at intervals on the surface of the active anti-fouling flexible drag reduction layer to obtain a passive anti-fouling elastic drag reduction layer, thereby preparing a multilayer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties.
[0027] In the microphase separation composite solution of the present invention, polyurethane, polysiloxane and catechol compounds have different solubilities in the mixed solvent, so microphase separation will occur, that is, the scale of phase separation is relatively small, and it still looks like a homogeneous solution macroscopically. Microphase separation is beneficial to constructing a drag reduction surface that imitates dolphin skin.
[0028] In some embodiments, the mixed solvent includes a combination of a polar solvent and a weak polar solvent, wherein the volume ratio of the polar solvent to the weak polar solvent is 1:9 to 9:1.
[0029] Furthermore, the polar solvent may be any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, etc., or a combination of two or more thereof, but is not limited thereto.
[0030] Furthermore, the weak polar solvent may be any one of tetrahydrofuran, toluene, chloroform, etc., or a combination of two or more thereof, but is not limited thereto.
[0031] In some embodiments, the first mixed reaction system includes 1-10 wt % of a silane coupling agent, 0.1-2 wt % of a two-dimensional sheet material, 0.1-5 wt % of nanoparticles, 5-20 wt % of an epoxy resin, and 5-20 wt % of a fluorocarbon resin.
[0032] In some embodiments, the silane coupling agent may include any one or a combination of two or more of aminopropyltriethoxysilane, octadecyltrimethoxysilane, isocyanatepropyltriethoxysilane, etc., but is not limited thereto.
[0033] In some embodiments, the two-dimensional sheet material may include any one or a combination of two or more of reduced graphene oxide, molybdenum disulfide, montmorillonite nanosheets, etc., but is not limited thereto.
[0034] Furthermore, the two-dimensional sheet material has a sheet diameter of 5nm~100µm, and the number of sheets is 1~5 layers.
[0035] In some embodiments, the nanoparticles may include any one or a combination of two or more of aluminum oxide, barium sulfate, silicon dioxide, etc., but are not limited thereto.
[0036] Furthermore, the particle size of the nanoparticles is 5-100 nm.
[0037] In some embodiments, the substrate may include at least any one of glass, plastic, and metal plate, but is not limited thereto.
[0038] In some embodiments, the temperature of the first reaction is 30-60°C, and the time of the first reaction is 1-24h. The mechanism of the first reaction in this step is that 1-10wt% of silane coupling agent, 0.1-2wt% of two-dimensional sheet material, 0.1-5wt% of nanoparticles, 5-20wt% of epoxy resin and 5-20wt% of fluorocarbon resin have different solubility in the solvent. According to the principle of similar compatibility, during the film formation process, each component spontaneously arranges and combines to form a film; and epoxy resin and fluorocarbon resin will level the film, while two-dimensional sheet materials and nanoparticles can only be dispersed in the solvent, and the leveling is poor. And the two-dimensional sheet material and nanoparticles are relatively large in size, and the combination of the two can form embedded protrusions on the film, that is, a hybrid connection layer with a peak-to-valley structure is obtained.
[0039] In some embodiments, the preparation method specifically includes: in a protective atmosphere, adding polyurethane to a mixed solvent, stirring to dissolve, and then adding a strong polar monomer and an initiator and stirring to carry out a second reaction to obtain the flexible composite hydrogel.
[0040] In some embodiments, the second mixed reaction system includes 5-30 wt % of polyurethane, 2-20 wt % of strong polar monomer, and 0.1-2 wt % of initiator.
[0041] In some embodiments, the strong polar monomer includes any one or a combination of two or more of acrylic acid, methacrylic acid, hydroxyethyl dimethacrylate, and the like, but is not limited thereto.
[0042] Furthermore, the initiator may be at least any one of azobisisobutyronitrile, azobisisoheptanenitrile, etc., but is not limited thereto.
[0043] In some embodiments, the stirring and dissolving is carried out at a temperature of 30 to 60° C. and for a time of 1 to 8 hours.
[0044] In some embodiments, the temperature of the second reaction is 60-100°C and the time is 2-24 hours. The mechanism of the second reaction in this step is that the strongly polar monomer undergoes free radical polymerization to generate a polymer, which is entangled with the polyurethane chain to generate a flexible composite hydrogel.
[0045] Further, the protective atmosphere may be a nitrogen atmosphere, but is not limited thereto.
[0046] In some embodiments, the preparation method specifically includes: coating the flexible composite hydrogel on the surface of the hybrid connection layer with a peak-valley structure, curing at 5-60°C for 5min-24h, then immersing in a metal salt aqueous solution, and reacting at 5-60°C for 10min-24h to obtain an active antifouling flexible drag reduction layer. In this step, the present invention utilizes the strong coordination effect between the carboxyl group of the strong polar monomer and the metal ion to significantly enhance the binding force of the metal ion, thereby constructing an active antifouling flexible drag reduction layer.
[0047] In some embodiments, the concentration of the metal salt contained in the metal salt aqueous solution is 1-20 wt %.
[0048] In some embodiments, the metal salt contained in the metal salt aqueous solution may include any one or a combination of two or more of copper chloride, zinc chloride, silver nitrate, etc., but is not limited thereto.
[0049] In some embodiments, the third mixed reaction system includes 5 to 30 wt % of polyurethane, 5 to 20 wt % of polysiloxane, and 0.1 to 5 wt % of a catechol compound.
[0050] In some embodiments, the catechol compound may include any one or a combination of two or more of dopamine, tannic acid, juglone, etc., but is not limited thereto.
[0051] In some embodiments, the temperature of the third reaction is 30-60°C and the time is 1-24 hours. The mechanism of the third reaction in this step is that polyurethane mainly provides flexibility, polysiloxane has low surface energy, which can hinder the attachment and deposition of pollutants, and due to the large difference in physicochemical properties between polyurethane and polysiloxane, it is difficult to form a homogeneous phase, so adding catechol compounds can improve the compatibility between the two phase interfaces.
[0052] In some embodiments, the preparation method specifically includes: placing a mask on the surface of the active anti-fouling flexible drag reduction layer, coating the microphase separation composite solution, and then curing to obtain the passive anti-fouling elastic drag reduction layer; wherein the pore size of the mask is 30~500µm and the thickness is 10~500µm.
[0053] In some embodiments, the curing temperature is 5-60° C. and the curing time is 5 min-24 h.
[0054] As one of the more specific embodiments, the method for preparing the multilayer composite material with multiple antifouling synergistic flexibility and enhanced drag reduction properties may include the following steps:
[0055] (1) adding 1-10 wt% of silane coupling agent, 0.1-2 wt% of two-dimensional sheet material, 0.1-5 wt% of nanoparticles, 5-20 wt% of epoxy resin and 5-20 wt% of fluorocarbon resin into a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (the volume ratio of the two is 1:9-9:1), stirring and reacting at 30-60° C. for 1-24 h, and applying the mixture on the surface of the substrate to obtain a hybrid connection layer with a peak-valley structure;
[0056] (2) Add 5-30 wt% polyurethane into a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of the two is 1:9-9:1), stir and dissolve at 30-60 °C for 1-8 h, add 2-20 wt% strong polar monomer and 0.1-2 wt% azobisisobutyronitrile, stir and react at 60-100 °C for 2-24 h, and protect with nitrogen throughout the process to obtain a flexible composite hydrogel;
[0057] (3) coating the flexible composite hydrogel prepared in step (2) on the hybrid connection layer with a peak-valley structure prepared in step (1), curing at 5-60° C. for 5 min-24 h, immersing in a 1-20 wt % aqueous solution of a metal salt, and reacting at 5-60° C. for 10 min-24 h to obtain an active antifouling flexible drag reduction layer;
[0058] (4) adding 5-30 wt% polyurethane, 5-20 wt% polysiloxane, and 0.1-5 wt% catechol compound into a mixed solvent consisting of N,N-dimethylformamide and tetrahydrofuran (the volume ratio of the two is 1:9-9:1), stirring and reacting at 30-60 °C for 1-24 h to obtain a microphase separation composite solution;
[0059] (5) Placing the mask on the active anti-fouling flexible drag reduction layer prepared in step (3), brushing the microphase separation composite solution prepared in step (4), and then curing at 5-60° C. for 5 min-24 h to obtain a passive anti-fouling elastic drag reduction layer.
[0060] In summary, the preparation method provided by the present invention first constructs a hybrid connection layer with a peak-valley structure on a substrate by a brushing method; then brushes a flexible composite hydrogel, and utilizes the strong coordination between its carboxyl group and metal ions to construct an active antifouling flexible drag reduction layer; finally, utilizes the characteristics of the mask plate to selectively construct a micro-region passive antifouling elastic drag reduction layer. The present invention synergizes the anchoring effect of the peak-valley structure of the hybrid connection layer, the drag reduction characteristics of the elastic drag reduction surface with thickness steps, and the active antifouling and passive antifouling to jointly reduce the problem of increased friction resistance caused by biological contamination, and obtain a stable drag reduction composite material.
[0061] As another aspect of the technical solution of the present invention, it also relates to a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties prepared by the aforementioned method.
[0062] See also Figure 1 As shown, in some preferred embodiments, the multilayer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties includes a bottom-up hybrid connection layer 2, an active anti-fouling flexible drag reduction layer 3, and a passive anti-fouling elastic drag reduction layer 4 built layer by layer on a substrate 1.
[0063] Furthermore, the hybrid connection layer comprises a plurality of peak-valley structures with protrusions. Specifically, the peak height of the peak-valley structure is 10nm~100µm, the peak width is 100nm~600µm; the trough depth is 5nm~100µm, and the trough width is 50nm~40µm. The hybrid connection layer with a peak-valley structure prepared by the present invention can improve the bonding strength of the active anti-fouling flexible drag reduction layer and the passive anti-fouling elastic drag reduction layer on the substrate, improve the stability of the drag reduction composite material, and extend the service life.
[0064] Furthermore, the thickness of the hybrid connection layer is 1-1000 μm.
[0065] Furthermore, the thickness of the active anti-fouling flexible drag reduction layer is 1-500 µm.
[0066] Furthermore, the passive anti-fouling elastic drag reduction layer includes a plurality of elastic drag reduction units arranged at intervals, the diameter of the elastic drag reduction unit is 30~500µm, the height is 10~500µm, and the interval distance between adjacent elastic drag reduction units is 1~1000µm. The present invention uses a mask plate to form an elastic drag reduction surface with a thickness step, and the thickness gradient and elasticity cooperate to adapt to the external flow field pressure, effectively suppress pressure pulsation, and absorb the kinetic energy of the external flow field acting on the elastic drag reduction layer, thereby increasing the upper limit of the Reynolds number and the stability of the boundary layer for the transition from laminar flow to turbulent flow in the external flow field, delaying the transition from laminar flow to turbulent flow, reducing friction resistance, and improving drag reduction capability. Due to the effect of the mask plate, a passive anti-fouling elastic drag reduction layer is constructed on the active anti-fouling flexible drag reduction layer, so a thickness gradient can be formed.
[0067] The multilayer composite material of the present invention adopts active antifouling and passive antifouling to block bacteria, barnacles, algae and other substances in seawater from forming conditional films on the surface of the drag reduction material, thereby inhibiting biological pollution and reducing the problem of increased friction resistance caused by biological pollution.
[0068] Furthermore, the multi-layer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties has a sterilization rate of more than 99.9% against Escherichia coli, and a drag reduction rate of 13.1% to 18.3% within 24 hours.
[0069] In summary, the multi-layer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties of the present invention has multiple layers with complementary advantages and multi-functional coupling, and finally obtains a high-performance and stable composite material, which can be used to achieve anti-fouling, drag reduction and speed-up of water vessels, underwater ships, etc.
[0070] Another aspect of the embodiments of the present invention further provides the application of the aforementioned multi-layer composite material with multiple anti-fouling and coordinated flexible enhanced drag reduction properties. Specifically, the multi-layer composite material can be used to achieve anti-fouling, drag reduction and speed increase for water vessels, underwater ships, etc.
[0071] The whole process is described in detail below through several embodiments and drawings, but the protection scope of the present invention is not limited by these embodiments. At the same time, the embodiments only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose. All variations associated with or derived from the contents disclosed in the present invention are considered to be within the protection scope of the present invention.
[0072] Example 1
[0073] (1) 1 wt% of a silane coupling agent, 0.1 wt% of a two-dimensional sheet material, 0.1 wt% of nanoparticles, 20 wt% of an epoxy resin, and 5 wt% of a fluorocarbon resin are added to a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (the volume ratio of the two is 1:9), stirred at 30° C. for 24 h, and applied on the surface of a substrate to obtain a hybrid connection layer having a peak-valley structure; wherein the silane coupling agent is aminopropyltriethoxysilane, the two-dimensional sheet material is reduced graphene oxide, the nanoparticles are aluminum oxide, and the substrate is glass;
[0074] (2) 5 wt% polyurethane was added into a mixed solvent of N,N-dimethylformamide and tetrahydrofuran (volume ratio of the two was 1:9), stirred and dissolved at 30 °C for 8 h, 2 wt% acrylic acid and 0.1 wt% azobisisobutyronitrile were added, stirred and reacted at 100 °C for 2 h, with nitrogen protection throughout the process, to obtain a flexible composite hydrogel;
[0075] (3) coating the composite hydrogel prepared in step (2) on the hybrid connection layer with a peak-valley structure prepared in step (1), curing at 5° C. for 24 h, immersing in a 1 wt % copper chloride aqueous solution, and allowing to react at 5° C. for 24 h to obtain an active antifouling flexible drag reduction layer;
[0076] (4) 5 wt% polyurethane, 5 wt% polysiloxane, and 0.1 wt% dopamine were added to a mixed solvent consisting of N,N-dimethylformamide and tetrahydrofuran (the volume ratio of the two was 1:9), and stirred at 30 °C for 1 h to obtain a microphase separation composite solution;
[0077] (5) Placing the mask on the active antifouling flexible drag reduction layer prepared in step (3), brushing the microphase separation composite solution prepared in step (4), and curing at 5° C. for 24 hours to obtain a passive antifouling elastic drag reduction layer, that is, a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties; the mask has an aperture of 500 μm and a thickness of 10 μm.
[0078] After a 24-hour water tunnel test, the drag reduction rate of the multilayer composite material prepared in this embodiment is 13.1%; the sterilization rate for Escherichia coli is 99.9%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms is less than 3%, and the drag reduction rate is 11.9%.
[0079] Example 2
[0080] (1) adding 10 wt% of a silane coupling agent, 2 wt% of a two-dimensional sheet material, 5 wt% of nanoparticles, 5 wt% of an epoxy resin and 20 wt% of a fluorocarbon resin into a mixed solvent of N,N-dimethylacetamide and tetrahydrofuran (the volume ratio of the two is 9:1), stirring and reacting at 60° C. for 1 h, and applying the mixture on the surface of a substrate to obtain a hybrid connection layer having a peak-valley structure; wherein the silane coupling agent is octadecyltrimethoxysilane, the two-dimensional sheet material is molybdenum disulfide, the nanoparticles are barium sulfate, and the substrate is plastic;
[0081] (2) 30 wt% polyurethane was added to a mixed solvent of N,N-dimethylacetamide and tetrahydrofuran (volume ratio of the two was 9:1), stirred and dissolved at 60 °C for 1 h, 20 wt% methacrylic acid and 2 wt% azobisisobutyronitrile were added, stirred and reacted at 60 °C for 24 h, with nitrogen protection throughout the process, to obtain a flexible composite hydrogel;
[0082] (3) coating the composite hydrogel prepared in step (2) on the hybrid connection layer with a peak-valley structure prepared in step (1), curing at 60° C. for 5 min, immersing in a 20 wt % zinc chloride aqueous solution, and reacting at 60° C. for 10 min to obtain an active antifouling flexible drag reduction layer;
[0083] (4) 30 wt% polyurethane, 20 wt% polysiloxane, and 5 wt% tannic acid were added to a mixed solvent consisting of N,N-dimethylacetamide and tetrahydrofuran (the volume ratio of the two was 9:1), and stirred at 60 °C for 24 h to obtain a microphase separation composite solution;
[0084] (5) Placing the mask on the active antifouling flexible drag reduction layer prepared in step (3), brushing the microphase separation composite solution prepared in step (4), and curing at 60° C. for 5 min to obtain a passive antifouling elastic drag reduction layer, that is, a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties is obtained; the mask has an aperture of 30 μm and a thickness of 500 μm.
[0085] After a 24-hour water tunnel test, the drag reduction rate of the multilayer composite material prepared in this embodiment is 17.8%; the sterilization rate of Escherichia coli is 99.9%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms is less than 1%, and the drag reduction rate is 17.3%.
[0086] Example 3
[0087] (1) 2 wt% of a silane coupling agent, 1 wt% of a two-dimensional sheet material, 4 wt% of nanoparticles, 15 wt% of an epoxy resin, and 18 wt% of a fluorocarbon resin are added to a mixed solvent of N-methylpyrrolidone and toluene (the volume ratio of the two is 4:6), stirred at 60° C. for 12 h, and applied to the surface of a substrate to obtain a hybrid connection layer having a peak-valley structure; wherein the silane coupling agent is isocyanate propyltriethoxysilane, the two-dimensional sheet material is montmorillonite nanosheets, the nanoparticles are silicon dioxide, and the substrate is a metal plate;
[0088] (2) 10 wt% polyurethane was added to a mixed solvent of N-methylpyrrolidone and toluene (volume ratio of the two was 3:7), stirred and dissolved at 60 °C for 2 h, 15 wt% hydroxyethyl dimethacrylate of isophthalic anhydride and 1.5 wt% azobisisoheptanenitrile were added, stirred and reacted at 80 °C for 14 h, with nitrogen protection throughout the process, to obtain a flexible composite hydrogel;
[0089] (3) coating the composite hydrogel prepared in step (2) on the hybrid connection layer with a peak-valley structure prepared in step (1), curing at 40° C. for 0.5 h, immersing in a 3 wt % silver nitrate aqueous solution, and reacting at 40° C. for 2 h to obtain an active antifouling flexible drag reduction layer;
[0090] (4) 10 wt% polyurethane, 8 wt% polysiloxane, and 4 wt% juglone were added to a mixed solvent consisting of N-methylpyrrolidone and toluene (the volume ratio of the two was 3:7), and stirred at 60 °C for 24 h to obtain a microphase separation composite solution;
[0091] (5) Placing the mask on the active antifouling flexible drag reduction layer prepared in step (3), brushing the microphase separation composite solution prepared in step (4), and curing at 40° C. for 1 h to obtain a passive antifouling elastic drag reduction layer, that is, a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties; the mask has an aperture of 100 μm and a thickness of 120 μm.
[0092] After a 24-hour water tunnel test, the drag reduction rate of the multilayer composite material prepared in this embodiment is 14.9%; the sterilization rate for Escherichia coli is 99.9%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms is less than 2% and the drag reduction rate is 13.5%.
[0093] Example 4
[0094] (1) 6 wt% of a silane coupling agent, 2 wt% of a two-dimensional sheet material, 2 wt% of nanoparticles, 18 wt% of an epoxy resin, and 10 wt% of a fluorocarbon resin are added to a mixed solvent of dimethyl sulfoxide and chloroform (the volume ratio of the two is 5:5), stirred at 50° C. for 8 h, and applied on the surface of a substrate to obtain a hybrid connection layer having a peak-valley structure; wherein the silane coupling agent is aminopropyltriethoxysilane, the two-dimensional sheet material is molybdenum disulfide, the nanoparticles are aluminum oxide, and the substrate is glass;
[0095] (2) 12 wt% polyurethane was added to a mixed solvent of dimethyl sulfoxide and chloroform (volume ratio of 4:6), stirred and dissolved at 45 °C for 3 h, 18 wt% acrylic acid and 1.5 wt% azobisisobutyronitrile were added, stirred and reacted at 70 °C for 9 h, with nitrogen protection throughout the process, to obtain a flexible composite hydrogel;
[0096] (3) coating the composite hydrogel prepared in step (2) on the hybrid connection layer with a peak-valley structure prepared in step (1), curing at 35° C. for 1 h, immersing in a 15 wt % copper chloride aqueous solution, and reacting at 40° C. for 6 h to obtain an active antifouling flexible drag reduction layer;
[0097] (4) 12 wt% polyurethane, 9 wt% polysiloxane, and 3 wt% dopamine were added to a mixed solvent of dimethyl sulfoxide and chloroform (the volume ratio of the two was 5:5), and stirred at 45 °C for 18 h to obtain a microphase separation composite solution;
[0098] (5) Placing the mask on the active antifouling flexible drag reduction layer prepared in step (3), brushing the microphase separation composite solution prepared in step (4), and curing at 30° C. for 20 h to obtain a passive antifouling elastic drag reduction layer, that is, a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties; the mask has an aperture of 150 μm and a thickness of 200 μm.
[0099] After a 24-hour water tunnel test, the drag reduction rate of the multilayer composite material prepared in this embodiment is 18.3%; the sterilization rate of Escherichia coli is 99.9%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms is less than 1%, and the drag reduction rate is 17.1%.
[0100] Comparative Example 1
[0101] This control example is basically the same as Example 4, except that: a hybrid connection layer with a peak-valley structure is not constructed. Without the hybrid connection layer with a peak-valley structure, the interaction force between the active antifouling flexible drag reduction layer and the substrate is extremely weak, easy to break and fall off, and the service life is short. After a 2-hour water tunnel test, the active antifouling flexible drag reduction layer and the passive antifouling elastic drag reduction layer have completely fallen off, and the material has failed.
[0102] Comparative Example 2
[0103] This control example is basically the same as Example 4, except that: in step (1), the concentration of the two-dimensional sheet material and the nanoparticles are reduced from 2wt% to 0wt%, and the prepared hybrid connection layer does not have a peak-valley structure. The anchoring effect of the smooth hybrid connection layer is significantly lower than that of the hybrid connection layer with a peak-valley structure, the interaction force between the active antifouling flexible drag reduction layer and the substrate is weak, and the service life is relatively short. After a 4-hour water tunnel test, the active antifouling flexible drag reduction layer and the passive antifouling elastic drag reduction layer have completely fallen off, and the material has failed.
[0104] Comparative Example 3
[0105] This control example is basically the same as Example 4, except that no active antifouling flexible drag reduction layer is constructed. After removing the mask, the passive antifouling elastic drag reduction layer can only cover part of the hybrid connection layer with a peak-valley structure. There are a large number of air pockets in the exposed hybrid connection layer with a peak-valley structure, and the drag reduction ability disappears with the disappearance of the air pockets. After a 10-minute water tunnel test, the drag reduction rate of the multilayer composite material was 8%; after a 24-hour test, the drag reduction rate of the composite coating was -13%, which means an increase in drag of 13%; the sterilization rate for Escherichia coli was 20%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms was greater than 30%, and the drag reduction rate dropped to -46%, which means an increase in drag of 46%.
[0106] Comparative Example 4
[0107] This control example is basically the same as Example 4, except that: in step (3), the concentration of the copper chloride aqueous solution is reduced from 15wt% to 0wt%, and the prepared active antifouling flexible drag reduction layer does not have active antifouling properties. After 24h water tunnel test, the drag reduction rate of the multilayer composite material is 10.2%; the sterilization rate of Escherichia coli is 2%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms is greater than 15%, and the drag reduction rate is reduced to -8.7%, that is, the drag increase is 8.7%.
[0108] Comparative Example 5
[0109] This control example is basically the same as Example 4, except that no passive antifouling elastic drag reduction layer is constructed. After 24 hours of water tunnel testing, the drag reduction rate of the multilayer composite material is 9.4%; the sterilization rate of Escherichia coli is 98%; after static immersion in the harbor for 3 months, the coverage area of hard-shell fouling organisms is greater than 20%, and the drag reduction rate is reduced to -22%, that is, the drag increase is 22%.
[0110] Comparative Example 6
[0111] This comparative example is basically the same as Example 4, except that: no mask plate is used, but the microphase separation composite solution prepared in step (4) is directly brushed on the active antifouling flexible drag reduction layer. The active antifouling flexible drag reduction layer is completely covered and becomes ineffective, and does not have active antifouling properties.
[0112] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification, referring to the methods of Examples 1 to 4, and also produced a high-performance, stable, multi-layer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties.
[0113] It should be understood that the above are only specific application examples of the present invention and do not constitute any limitation on the protection scope of the present invention. Any technical solution formed by equivalent transformation or equivalent replacement falls within the protection scope of the present invention.
Claims
1. A method for preparing a multilayer composite material with multiple antifouling and flexible enhanced drag reduction properties, characterized in that: include: A first mixed reaction system comprising a silane coupling agent, a two-dimensional sheet material, nanoparticles, an epoxy resin, a fluorocarbon resin and a mixed solvent is subjected to a first reaction and applied to a surface of a substrate to obtain a hybrid connection layer having a peak-valley structure, wherein the mixed solvent is a combination of a polar solvent and a weak polar solvent, wherein the volume ratio of the polar solvent to the weak polar solvent is 1:9-9:1, and the first mixed reaction system comprises 1-10wt% of a silane coupling agent, 0.1-2wt% of a two-dimensional sheet material, 0.1-5wt% of nanoparticles, 5-20wt% of an epoxy resin and 5-20wt% of a fluorocarbon resin; the hybrid connection layer comprises a plurality of peak-valley structures having a protrusion shape; the peak height of the peak-valley structure is 10nm-100µm, and the peak width is 100nm-600µm; the valley depth is 5nm-100µm, and the valley width is 50nm-40µm; the thickness of the hybrid connection layer is 1-1000µm; A second mixed reaction system comprising polyurethane, a strong polar monomer, an initiator and a mixed solvent is subjected to a second reaction in a protective atmosphere to obtain a flexible composite hydrogel; and the flexible composite hydrogel is applied to the surface of a hybrid connection layer having a peak-valley structure, cured, and then immersed in a metal salt aqueous solution for static reaction to obtain an active antifouling flexible drag reduction layer, wherein the second mixed reaction system comprises 5-30wt% of polyurethane, 2-20wt% of a strong polar monomer and 0.1-2wt% of an initiator, wherein the strong polar monomer is selected from any one of acrylic acid, methacrylic acid and hydroxyethyl dimethacrylate of phthalic anhydride or a combination of two or more thereof; the concentration of the metal salt contained in the metal salt aqueous solution is 1-20wt%; and the thickness of the active antifouling flexible drag reduction layer is 1-500µm; A third mixed reaction system comprising polyurethane, polysiloxane, a catechol compound and a mixed solvent is subjected to a third reaction to obtain a microphase separation composite solution; a mask is placed on the surface of the active antifouling flexible drag reduction layer, and the microphase separation composite solution is coated, and then cured, thereby forming elastic drag reduction units arranged at intervals on the surface of the active antifouling flexible drag reduction layer to obtain a passive antifouling elastic drag reduction layer, and a multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties is obtained; wherein the aperture of the mask is 30-500 μm, the thickness is 10 ~500µm; the third mixed reaction system includes 5~30wt% of polyurethane, 5~20wt% of polysiloxane and 0.1~5wt% of catechol compound, and the catechol compound is selected from any one or a combination of more than two of dopamine, tannic acid and juglone; the passive anti-fouling elastic drag reduction layer includes a plurality of elastic drag reduction units arranged at intervals, and the diameter of the elastic drag reduction unit is 30~500µm and the height is 10~500µm; the interval distance between adjacent elastic drag reduction units is 1~1000µm.
2. The preparation method according to claim 1, characterized in that: The polar solvent includes any one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide, or a combination of two or more thereof; And / or, the weak polar solvent includes any one of tetrahydrofuran, toluene, and chloroform, or a combination of two or more thereof.
3. The preparation method according to claim 1, characterized in that: The silane coupling agent includes any one of aminopropyltriethoxysilane, octadecyltrimethoxysilane and isocyanatepropyltriethoxysilane or a combination of two or more thereof.
4. The preparation method according to claim 1, characterized in that: The two-dimensional sheet material includes any one or a combination of two or more of reduced graphene oxide, molybdenum disulfide, and montmorillonite nanosheets; And / or, the two-dimensional sheet material has a sheet diameter of 5nm~100µm, and the number of sheets is 1~5.
5. The preparation method according to claim 1, characterized in that: The nanoparticles include any one of aluminum oxide, barium sulfate, and silicon dioxide, or a combination of two or more thereof; And / or, the particle size of the nanoparticles is 5-100 nm.
6. The preparation method according to claim 1, characterized in that: The substrate includes at least any one of glass, plastic, and metal plate; And / or, the temperature of the first reaction is 30-60° C., and the time is 1-24 hours.
7. The preparation method according to claim 1, characterized in that: include: In a protective atmosphere, polyurethane is added to a mixed solvent and stirred to dissolve, and then a strong polar monomer and an initiator are added and stirred to carry out a second reaction to obtain the flexible composite hydrogel.
8. The preparation method according to claim 7, characterized in that: The initiator includes at least any one of azobisisobutyronitrile and azobisisoheptanenitrile; And / or, the stirring and dissolving is performed at a temperature of 30 to 60° C. and for a time of 1 to 8 hours; And / or, the temperature of the second reaction is 60-100° C., and the time is 2-24 hours; And / or, the protective atmosphere comprises a nitrogen atmosphere.
9. The preparation method according to claim 1, characterized in that: include: The flexible composite hydrogel is coated on the surface of the hybrid connection layer with a peak-valley structure, cured at 5-60° C. for 5 min-24 h, then immersed in a metal salt aqueous solution, and allowed to react at 5-60° C. for 10 min-24 h to obtain an active antifouling flexible drag reduction layer; And / or, the metal salt contained in the metal salt aqueous solution includes any one of copper chloride, zinc chloride, and silver nitrate, or a combination of two or more thereof.
10. The preparation method according to claim 1, characterized in that: The temperature of the third reaction is 30-60° C. and the time is 1-24 hours.
11. The preparation method according to claim 1, characterized in that: The curing temperature is 5-60° C. and the curing time is 5 min-24 h.
12. A multilayer composite material with multiple antifouling synergistic flexibility and enhanced drag reduction properties prepared by the preparation method according to any one of claims 1 to 11, characterized in that: The multilayer composite material with multiple antifouling coordinated flexible enhanced drag reduction properties comprises a hybrid connection layer, an active antifouling flexible drag reduction layer and a passive antifouling elastic drag reduction layer which are sequentially stacked on a substrate.
13. The multi-layer composite material with multiple antifouling coordinated flexibility and enhanced drag reduction properties according to claim 12, characterized in that: The multi-layer composite material with multiple anti-fouling synergistic flexible enhanced drag reduction properties has a sterilization rate of more than 99.9% against Escherichia coli, and a drag reduction rate of 13.1% to 18.3% within 24 hours.
14. Use of the multilayer composite material with multiple antifouling synergistic flexible enhanced drag reduction properties as claimed in claim 12 or 13 in the field of antifouling or drag reduction and speed increase.
Citation Information
Patent Citations
Oil tank protective coating
CA2431599A1
Underwater self-repairing organic silicon antifouling coating and preparation method thereof
CN112552725A
Double-layer composite membrane type anti-fouling and anti-drag material and preparation method thereof
CN115838491A
Composite elastic anti-drag coating with multi-layer structure as well as preparation method and application of composite elastic anti-drag coating
CN117160824A
Marine anti-corrosion and anti-fouling polyurethane coating as well as preparation method and application thereof
CN118027795A
